A taxonomic study of Sorocephalus and Spatalla - Rourke, John Patrick (Department of Biological Sciences, 2023)
A brief historical review of previous taxonomic studies on Leucospermum is given. The principal diagnostic characters used in the present revision are evaluated. A complete taxonomic revision of the genus has been tinder taken. All the relevant names have been typified and all the type specimens have been personally examined, except in a few cases where no type of material could be traced. For each species the synonymy is given, the diagnostic characters are enumerated, brief historical comments are made where relevant and short ecological observations are provided. The distribution ranges. of all taxa recognized have been mapped. ·In the present study, 47 species are upheld, arranged in 9 sections. 8 new species, L. innovans, L. pluridens, L. praecox, L. fulgens, L. erubescens, L. utriculosum, L. profugum and L. secundifolium are described. A key to the species is provided. Mass gatherings have been used in several cases to investigate' the variation ranges in complex groups. All but 3 taxa have been studied in the field. Although much of the variation in the polymorphic species L. cuneiforme appears to be random, a topocline in respect of leaf width was observed. Leaf width was found to increase from east to west over the distribution range of L. cuneiforme. A reappraisal of the taxonomic status of several complex vicarious populations was made, particularly those now upheld as L. profugum and L. spathulatum, praecox and L. fulgens L. catherinae and L. formosum, L. calligerum and L. wittebergense and L. alpinum and L. obtusatum. An ecocline in the species here delimited as L. oleaefolium is described. To demonstrate the cline, samples were obtained along a transect, over an altitudinal (and also ecological) gradient. When mass gatherings, made at intervals along the transect,were evaluated, continuous variation in respect of growth habit, leaf pubescence and in the length and pubescence of the involucral bracts, was observed. Chromosome counts for 16 species of Leucespermum are listed, 13 of which were made by the present author. The somatic number is 2n = 24 Observations on the reaction of certain species to burning are discussed. The majority of species of Leucospermum have no special adaptation to burning, regeneration taking place from the seeds. A few species are able to regenerate from the aerial stems, but their survival rate is rather low and depends on the severity of the fire. The most effective adaptation to burning is the persistent rootstock or lignotuber. Development of the lignotuber was found to commence in the seedling stage, a few months after germination. Studies on the pollination biology of the genus led the author to conclude tha.t Promerops cafer (the Cape Sugar bird) and three species of sunbird, Anthobaphes violacea, Nectarina famosa and Cinnyris chalybeus were the most important pollen vectors. Certain Scarab beetles, particularly Anisonyx ursus and. Trichostetha spp. · were found to play a significant but less important role in pollen transfer due to their short seasonal activity. Phytogeographic studies showed that although the distribution range of Leucospermum extends as far north as Rhodesia, the greatest species density is found in a narrow belt along the southern Cape coastal flats where 30% of the known species occur. A high proportion of geographical and edaphic vicariads occur within this coastal belt, the surface of which has been disturbed by marine regressions and invasions since the Tertiary. It is suggested that this zone has been an important area of speciation since the Pleistocene. The isolation and subsequent differentiation of certain montane populations such as L. spathulatum and L. profugum, L. calligerum and L. wittebergense, L. alpinum and L. obtusatum, is thought to have been caused by climatic fluctuations resulting from the hypothermal and hyperthermal phases during the Pleistocene. In the light of available paleoclimatological evidence, the distribution of certain species of the section Crassicaudex occuring in the summer rainfall regions of southern Africa, suggests that these taxa have been in existence since the Early Tertiary. It is suggested that. the species occuring in the southwestern Cape could have been derived from forms such as presently survive in south central Africa.